Research on the Impact of the Credibility of Live Broadcast Marketing’s Reputation on Consumers’ Purchase Intention - Lyu , Xingyu; Niyomsilp, Eksiri (Journal of Roi Kaensarn Academi, 2021)
Through combing and summarizing the literature, starting from the perspective of credibility, construct a theoretical model to study the influence of online word-of-mouth sources and information content on consumer purchase intentions, and analyze the cognitive needs in the credibility of online by means of interviews from demographic groups interested in cross-border e-commerce businesses. Word-of-mouth sources and information credibility the moderating effect between the degree of purchase and consumers’ purchase intention. The results found that: the professionalism of the reviewers, the motivation of the reviewers, the quality of the reviews and the number of reviews all positively promote consumers’ purchase intention. Cognitive needs have a significant positive moderating effect between source credibility, information credibility and consumer purchase intentions. Finally, suggestions are made to promote product marketing.